2018
DOI: 10.1186/s12957-018-1456-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient Blood Management improves outcome in oncologic surgery

Abstract: BackgroundPatient Blood Management (PBM) is a systematic quality improving clinical model to reduce anemia and avoid transfusions in all kinds of clinical settings. Here, we investigated the potential of PBM in oncologic surgery and hypothesized that PBM improves 2-year overall survival (OS).MethodsRetrospective analysis of patients 2 years before and after PBM implementation. The primary endpoint was OS at 2 years after surgery. We identified a sample size of 824 to detect a 10% improvement in survival in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…With the development of new medical technology, like neoadjuvant chemoradiotherapy, the possibility of allogeneic RBC transfusion is increasing [17]. Allogeneic RBC transfusion can improve the outcome in recipients by establishing blood volume, improving blood perfusion, and changing the gut microbiome [2,[18][19][20][21][22][23][24][25]. However, allogeneic RBC transfusion can also expose recipients to a chance of immunosuppression or poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of new medical technology, like neoadjuvant chemoradiotherapy, the possibility of allogeneic RBC transfusion is increasing [17]. Allogeneic RBC transfusion can improve the outcome in recipients by establishing blood volume, improving blood perfusion, and changing the gut microbiome [2,[18][19][20][21][22][23][24][25]. However, allogeneic RBC transfusion can also expose recipients to a chance of immunosuppression or poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The concept comprises more than 100 individual measures, which form the three sustaining pillars of PBM: (1) management of preoperative anaemia, (2) minimization of blood loss and (3) the rational use of allogenic blood products . It has been repeatedly demonstrated that the implementation of PBM into clinical routine reduces anaemia and transfusion rates, length of hospital stay, morbidity and mortality . Anaemia, defined by the World Health Organization (WHO) as a haemoglobin (Hb) level <12 g/dl in women and <13 g/dl in men , is a major predictor for higher perioperative transfusion requirements, prolonged length of stay in hospital and morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…It comprises a series of measures and methods to maintain an optimal haemoglobin (Hb) level, optimise haemostasis, minimise blood loss, and limit blood transfusions aiming to improve patient outcomes. Recent studies have shown that the use of PBM minimizes perioperative bleeding, reduces the requirement of blood transfusion [1][2][3][4][5][6][7][8], perioperative morbidity [1][2][3][4], mortality, duration of hospitalization [1,4], and costs [9,10]. Regarding this, the World Health Organization (WHO) was recommending since 2010 to urgently implement PBM [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this, the World Health Organization (WHO) was recommending since 2010 to urgently implement PBM [11]. Some hospitals have already successfully implemented PBM notably in Australia [7], Europe [2,[4][5][6], United States [3], and also in Asia. However, many obstetricians and obstetrical departments still are in need of guidance for the implementation of PBM in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%